Seasonality and varietal preference of red pumpkin beetle (Raphidopalpa Joveicollis) on cucumber (Cucumis sativus) in Assam - BORAH, R K (The Indian Journal of Agricultural Sciences, 2013)
A study was carried out during 1993-95 to observe the effect of different sowing seasons (summer, rainy and winter) and varieties ’AAUC I’, ’AAUC 2’ and ’Diphu Local’ cucumber (Cucumis sativus L.) on the infestation of red pumpkin beetle (Raphidopalpa .foveicollis L.) under hill zone of Assam. The maximum yield (9 830 kg/ha) was obtain od tained from the summer, 20 March sown crop with ’AAUC I’ cucumber with 2.8 beetles/plant and 33.3% plant damage followed by ’AAUC 2’ as well as ’Diphu Local’ cucumber of the same sowing season.